Never take your rhino on a plane [book with audioplayer] - Lewis, K. E. (Library Ideas, LLC, 2025)
A zany picture book packed with rhythm, rhyme, and rambunctiousness about the nonsense you might expect if you take your pet rhino on a plane. For fans of Mo Willems's Don't let the pigeon drive the bus! and Aaron Blabey's Piranhas don't eat bananas. You can take him on a ship, hail a taxi for the trip, waltz him gladly to the car or to the train -- but absolutely never believe it safe or clever to take your pet rhinoceros on a plane. A cautionary tale about the daredevil stunts and embarrassing antics you will face when traveling with your pet rhinoceros. From the security line to the luggage carousel, there is no hope for a relaxing trip or in-flight movie in this hilarious picture book. Young readers will laugh at the silliness and fun illustrations, while their caregivers will recognize the humor and perhaps even relate to the wild ride that ensues. With expressive, laugh-out-loud illustrations and lyrical writing that pays homage to nonsense poetry, Never take your rhino on a plane is a perfect read-aloud pick.